2018
DOI: 10.1021/acsbiomaterials.8b00489
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Antioxidant CeO2 Nanoparticles via Polyelectrolyte Microcapsules

Abstract: Cerium oxide nanoparticles (nanoceria) are regarded as one of the most promising inorganic antioxidants for biomedical applications. Considering nanoceria as a potential therapeutic agent, we aimed to develop a robust system for its intracellular delivery using layer-by-layer polyelectrolyte microcapsules. We have shown that citrate-stabilized cerium oxide nanoparticles can be effectively incorporated into the structure of polyelectrolyte microcapsules made from biodegradable and nonbiodegradable polymers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 72 publications
(91 reference statements)
0
25
0
Order By: Relevance
“…32 On the other hand, CNPs were known as antioxidants because of their dual redox states on the surface. [33][34][35] Antioxidants could be harmful per se, because of pro-oxidant activity. [36][37][38] For example, Srinivas et al suggested that acute exposure of CNPs through inhalation route may induce cytotoxicity via oxidative stress and may lead to a chronic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…32 On the other hand, CNPs were known as antioxidants because of their dual redox states on the surface. [33][34][35] Antioxidants could be harmful per se, because of pro-oxidant activity. [36][37][38] For example, Srinivas et al suggested that acute exposure of CNPs through inhalation route may induce cytotoxicity via oxidative stress and may lead to a chronic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The LbL method allows the integration of CeO 2 nanoparticles by replacing one of the polyelectrolyte layers [ 101 ]: bare CeNPs in solution have a positive ζ-potential and thus can replace a polycation layer during microcapsule synthesis; conversely, carboxylic (citric, polyacrylic) acids normally used for the stabilization of cerium oxide nanoparticles provide a negative ζ-potential, and these particles can be incorporated into the microcapsule shell in place of one of the polyanion layers. The experiments in vitro on B50 neuroblastoma cells confirmed nanoceria delivery into the cell, so that polymeric LbL microcapsules can be considered to be an efficient intracellular delivery system for therapeutic nanoparticles [ 102 ].…”
Section: Polymeric Composites With Ceria Nanoparticles For Drug Dementioning
confidence: 99%
“…X-ray radioprotective nanoceria was also previously incorporated into the polyelectrolyte shell of DS/pARG PEMCs. The PEMC acts to preserve the antioxidant effects of cerium and release it intracellularly in a controlled manner [244][245][246]. Cerium oxide acts as a reactive oxygen species scavenger and may also act as a "filter" within the PEMC shell, filtering out ROS and protecting its cargo, as shown through the protection of the encapsulated enzyme luciferase [247].…”
Section: Functionalisation With Nanoparticlesmentioning
confidence: 99%